Persepsi Siswa Sekolah Menengah Pertama terhadap Penggunaan Instagram sebagai Media Layanan Informasi Bimbingan dan Konseling - Andani, Melia Fitri; Lasan, Blasius Boli; Apriani, Rizka (citeus, 2025)
Instagram is an information technology that is used as a media for guidance and counseling information services during the Covid-19 pandemic. This study aims to find out how students perceive the use of Instagram as a medium for guidance and counseling information services. This study uses a qualitative approach using phenomenological studies. Data collection procedures through structured interview techniques, observation and documentation. Three research subjects were selected through a purposive sampling technique by applying several criteria. The subject criteria are students of SMP Negeri 9 Malang, have an Instagram account, follow the guidance and counseling Instagram account of SMP Negeri 9 Malang, and actively like posts on the guidance and counseling Instagram account of SMP Negeri 9 Malang. Checking the validity of the data in this study was carried out using source triangulation and technical triangulation. The results showed that students had a positive perception of the use of Instagram as a medium for guidance and counseling information services in terms of cognitive, conative and affective components. The cognitive component includes students who are very familiar with Instagram and information services as well as Instagram's positive opinions for school purposes as a medium for guidance and counseling information services. The conative component of students often access Instagram and Instagram Guidance and Counseling. The affective component includes the background of following Instagram guidance and counseling to meet the needs and pleasure of receiving information services through Instagram.